Signaling versus Auditing - Helmut Bester; Matthias Lang; Jianpei Li (The RAND Journal of Economics, 2021)
We analyze a competitive labor market in which workers signal their productivities through education, and firms have the option of auditing to learn workers' productivities. Audits are costly and non-contractible. We characterize the trade-offs between signaling by workers and costly auditing by firms. Auditing is always associated with (partial) pooling of worker types, and education is used as a signal only if relatively few workers have low productivity. Our results feature new auditing patterns and explain empirical observations in labor economics like wage differentials and comparative statics of education choices. Our analysis applies also to other signaling problems, for example, the financial structure of firms, warranties, and initial public~offerings.
Keywords: 330